2021
DOI: 10.1128/aac.01135-20
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events Associated with Nifurtimox Treatment for Chagas Disease in Children and Adults

Abstract: BACKGROUND: Nifurtimox (NF) is one of the only two drugs currently available for Chagas disease (ChD) treatment. However, there is scarce data on NF safety, and many physicians defer or refuse NF treatment because of concerns about drug tolerance. METHODS: Retrospective study of adverse drug reactions (ADRs) associated with NF treatment of ChD. Children received NF doses of 10-15 mg/kg/day for 60-90 days, and adults 8-10 mg/kg/day for 30 days. Results: 215 children (median age: 2.6yrs, range 0-17) and 105 adul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
4
10
1
Order By: Relevance
“…However, FDA-approved drugs can be used for nonapproved indications (i.e., off-label use), in accordance with the practice of medicine. The frequency of adverse events in adults and the most common adverse events and systems affected in children, adolescents, and adults were consistent with those reported in previous studies ( 3 – 7 ). The clinical study cited in the FDA approval of nifurtimox (Lampit) did not include adults but found that adverse events were more frequent in adolescents (aged 12 to <18 years) compared with younger age groups ( 8 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, FDA-approved drugs can be used for nonapproved indications (i.e., off-label use), in accordance with the practice of medicine. The frequency of adverse events in adults and the most common adverse events and systems affected in children, adolescents, and adults were consistent with those reported in previous studies ( 3 – 7 ). The clinical study cited in the FDA approval of nifurtimox (Lampit) did not include adults but found that adverse events were more frequent in adolescents (aged 12 to <18 years) compared with younger age groups ( 8 ).…”
Section: Discussionsupporting
confidence: 90%
“…Children and adolescents treated under the CDC IND were older (median age = 17 years) and reported more adverse events than in that study (90% versus 64.5%) ( 8 ). Among all age groups, the percentage of severe adverse events was higher than that described in other reports (10.4% versus 3.2%–5.1%) ( 5 , 6 ), including among children (13.3% versus 0.9%–1.6%) ( 3 , 8 ). These differences might be because of the way in which adverse events were reported, treatment dose differences, and older ages of children treated with nifurtimox under CDC’s protocol.…”
Section: Discussioncontrasting
confidence: 66%
“…Treatment discontinuation with NFX was only reported in two studies, which were 10.7% and 0%, respectively. Other studies have reported treatment discontinuation with NFX at 20% [ 34 ], 9.9% [ 35 ], and 9.7% [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been some concerns about the safety of NF. In a previous study, we demonstrated that NF is a safe option for ChD treatment ( 4 ). In this study, we systematically assessed the effectiveness of NF considering the same ChD cohort population, which included both children and adult patients with a long-term follow-up of more than 10 years.…”
Section: Introductionmentioning
confidence: 93%